The Role of Community Behavior in Mangrove Natural Resource Management: A Case Study in Kota Pari Village - Daulay, Muhammad Toyib; Faried, Annisa Ilmi; Matondang, Edi Saputra; Riwanda, Febby (Universitas Negeri Medan, 2023)
This study aims to ascertain and analyze the effect of community behavior on the mangrove natural resource management strategy in Kota Pari Village, Pantai Cermin District, Serdang Bedaga Province. Conservation efforts on mangrove forests have significant significance in relation to the function and role of mangroves, as they comprise physical, biological, ecological, and socioeconomic roles. The management of mangrove forests in multiple regions has had a substantial impact on the ecosystem. As a result, mangrove forest areas must be investigated in detail, in depth, and as soon as possible, as it is common knowledge that various development activities conducted in mangrove forest areas have resulted in a number of quite complex and concerning problems. According to the findings of this study, community behavior has a positive and significant impact on policy strategies. Positive and significant effects of community behavior on the management of mangrove forest natural resources. The management of mangrove natural resources is impacted positively and significantly by policy strategies. Through Policy Strategies, community behavior has a positive and significant impact on the management of mangrove forest natural resources. On the basis of the findings of this study, it is anticipated that residents of Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency will be able to increase the income of low-income residents.